Pendampingan Edukasi Transaksi Keuangan Untuk Meningatkan Literasi keuangan di BMT Maslahah Purwosari Pasuruan - Hotima, Husnul; Muhammad Nizar; Renita Firnanda Putri; Alviyaning Tiyas, Siti (LP3M IAIFA Kediri, 2024)
This community service aims to enhance financial literacy through educational assistance in financial transactions at BMT Maslahah Purwosari, Pasuruan. The primary issue addressed is the low level of understanding among BMT members regarding financial management, Islamic financing products, and secure financial transactions. The focus of this initiative is to provide education on the fundamental concepts of financial transactions based on sharia principles to improve the local community's financial understanding and skills. The method used in this community service is a participatory approach, involving direct mentoring and discussions with BMT members. This approach is designed to facilitate better comprehension of personal financial management and the utilization of financial products in accordance with sharia principles. The results of this community service demonstrate an improvement in the financial transaction skills and understanding of BMT Maslahah members, as well as increased awareness of the importance of prudent financial planning. This educational effort has brought about positive changes in the structured management of finances, grounded in sound financial principles, which are expected to contribute to the economic well-being of the community around the BMT.